Genome-Wide SNP Linkage Screen for Intracranial Aneurysm Susceptibility Genes: Results from 333 Multiplex IA Families - Vinall, Phil (MD Conference Express, 2008)
Genetic risk factors are considered important in the development, growth, and rupture of intracranial aneurysms (IAs). However, few of these risk factors have been identified. The Familial Intracranial Aneurysm [FIA] Study is a collaborative research effort of neurologists and neurosurgeons throughout the United States, Canada, Australia, and New Zealand that is studying genetic factors in 475 families with multiple IA-affected members.